A magyar külkereskedő vállalatok - Gábor Békés; László Halpern; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2011)
– This paper presents the specificities of Hungarian foreign trading firms from different perspectives, like concentration, efficiency and sectoral structure. Hungarian trade is highly concentrated similarly to other countries. Trading firms are more efficient than their non-trading peers, exporting firms lead the ranking. The trading status is more important in the efficiency ranking than the domestic vs. foreign ownership. This has primary relevance to policies, as they should remove all the barriers what firms confront when entering foreign markets in order to enhance productivity.
Keywords: D24; F14; L25; 330; foreign trade; total factor productivity; firms in Hungary; Außenhandel; Produktivität; Ungarn